IMPLEMENTASI PROJEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) KURIKULUM MERDEKA TEMA KEARIFAN LOKAL DALAM PENGUATAN KARAKTER PESERTA DIDIK DI SEKOLAH DASAR - Umi Latifah; Tri Joko Raharjo; Agus Yuwono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Observation results show the moral degradation of students that occurs in the world of education, such as bullying, violence, and a hedonistic lifestyle that is starting to spread. A sense of nationalism and understanding local culture is not necessary because students tend to be interested in foreign culture. The incoming foreign culture slowly erodes national identity, making students forget the applicable norms and ethics as well as the cultural values ​​taught. The aim of this research is to analyze the implementation of the Project for Strengthening the Profile of Pancasila Students (P5) independent curriculum with the theme of local wisdom in strengthening the character of students in elementary schools, obstacles, and alternative solutions. The approach used in this research is a qualitative approach. Looking at the problem formulation and the objectives to be achieved, the researcher used a qualitative research method, case study type. The presence of the Pancasila Student Profile Strengthening Project (P5) is a defense so that values, traditions, and culture become a fortress to strengthen the character of students so that they are not eroded by negative cultures.